Genetic variability analysis for growth and yield parameters in double cross maize (Zea mays l.) genotypes in Kitale county of Kenya - Melil, Charles K.; Ombakho, George; Omari, Odongo M.; Njoka, Fredrick M. (Science Journals Publishing, 2013)
Present study was conducted to select hybrids with improved yield, to identify testers for grain yield and to determine the magnitude of genetic variability in maize hybrids for yield and its elements. Adaptability of double cross hybrids was studied under varying agro-climatic conditions of parts of Western Kenya. Seventeen experimental hybrids and one commercial maize variety (standard) were planted in a 6x6 balanced lattice design with three replicates. Physiological and agronomic traits were observed and recorded from germination to maturity. Collected data was subjected to analysis of variance (ANOVA) using the general linear model SAS. The results showed that ear height ranged between 169.0 and 214.0 cm showed by genotype (95xF)x(50x82) and (95x8)x(50x16) respectively. The plant height ranged between 309.0 and 330.7 cm showed by genotype (44xA)x(50x93) and (44xA)x(82x93) respectively, grain weight ranged between 253.3 and 441.7 g showed by genotype (44xA)x(82x93) and (64x8)x(82x93) respectively, rows per cob ranged between 12.3 and 13.9 showed by genotype (95xF)x(82x16) and (Fx82)x(93x16) respectively. Grains per row ranged between 34.3 and 42.1 which was shown by genotype (AxF) x (50x82) and (95x8)x(50x16) respectively, the cob length ranged between 19.6 cm and 23.4 cm shown by genotype (56x44)x(50x93) and (95x8)x(50x16) respectively and the grain yield ranged between 5.2 and 12.8 t/ha produced by genotypes (95xF)x(82x16) and (56x44)x(50x16) respectively. Evaluating the various results revealed that genotype (56x44)x(50x16) and (95x8)x(50x16) were the most promising and their adaptation to the agro-ecological condition to this area can bring a substantial increase in maize grain yield.
Keywords: Genetic variation; Genotype; yield parameters; maize